2021
DOI: 10.48550/arxiv.2101.00981
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Coherence and Concentration in Tightly-Connected Networks

Abstract: The ability to achieve coordinated behaviorengineered or emergent-on networked systems has attracted widespread interest over several fields. This interest has led to remarkable advances in developing a theoretical understanding of the conditions under which agents within a network can reach an agreement (consensus) or develop coordinated behavior, such as synchronization. However, much less understood is the phenomenon of network coherence. Network coherence generally refers to nodes' ability in a network to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Recent work [11], [12] has shown that, under mild assumptions, the following holds 1 for almost any s 0 ∈ C,…”
Section: Preliminaries a Network Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…Recent work [11], [12] has shown that, under mild assumptions, the following holds 1 for almost any s 0 ∈ C,…”
Section: Preliminaries a Network Modelmentioning
confidence: 99%
“…Recently, it has been theoretically established that coherence naturally emerges when a group of nodes are tightlyconnected, regardless of the node dynamics, as long as the interconnection remains stable [11], [12]. The analysis also provides an asymptotically (as the network connectivity increases) exact characterization of the coherent response, H. Min and E. Mallada are with the Department of Electrical and Computer Engineering, Johns Hopkins University, Baltimore, MD 21218, USA{hanchmin, mallada}@jhu.edu.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations